2020
DOI: 10.3114/fuse.2020.05.06
|View full text |Cite
|
Sign up to set email alerts
|

Diatomophthoraceae – a new family of olpidiopsis-like diatom parasitoids largely unrelated to Ectrogella

Abstract: The oomycete genus Ectrogella currently comprises a rather heterogeneous group of obligate endoparasitoids, mostly of diatoms and algae. Despite their widespread occurrence, little is known regarding the phylogenetic affinities of these bizarre organisms. Traditionally, the genus was included within the Saprolegniales, based on zoospore diplanetism and a saprolegnia/achlya-like zoospore discharge. The genus has undergone multiple re-definitions in the past, and has often been used largely indiscriminately fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 20 publications
0
29
1
Order By: Relevance
“…Even though monophyly of the parasites of red algae was not resolved in Badis et al 2019, a monophyletic grouping was observed in Buaya et al (2019c) and Buaya and Thines (2020). Interestingly, the genus Ectrogella with its type species E. bacillariacearum, which was previously speculated to belong to the early-diverging lineages, was found to be embedded in the basal Saprolegniomycetes (Buaya and Thines 2020) and epitypified with a specimen exhibiting the typical thallus and exit-pore morphology described for the species by Zopf (1884). Consequently, the olpidiopsis-like (i.e.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Even though monophyly of the parasites of red algae was not resolved in Badis et al 2019, a monophyletic grouping was observed in Buaya et al (2019c) and Buaya and Thines (2020). Interestingly, the genus Ectrogella with its type species E. bacillariacearum, which was previously speculated to belong to the early-diverging lineages, was found to be embedded in the basal Saprolegniomycetes (Buaya and Thines 2020) and epitypified with a specimen exhibiting the typical thallus and exit-pore morphology described for the species by Zopf (1884). Consequently, the olpidiopsis-like (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…Miracula helgolandica was inferred to Section Editor: Marc Stadler be the earliest-diverging oomycete lineage together with the recently described freshwater parasitoid M. moenusica, while D. drebesii formed a monophyletic group together with D. gillii and uncultured environmental sequences (Buaya and Thines 2019;Buaya et al 2017;2019a). Only recently, phylogenetic affinities of the genus Olpidiopsis and Ectrogella were resolved and their type species epitypified, leading to the taxonomic revisions of these two important taxa of early-diverging oomycetes (Buaya et al 2019c; Buaya and Thines 2020). The genus Olpidiopsis with its type species O. saprolegniae was found to be unrelated to the parasites of red algae and diatoms parasitoids (Buaya et al 2019c).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations